Processing monitoring and data acquisition / Anita Kamaruddin and Mazida Mahmud - Kamaruddin, Anita; Mahmud, Mazida (1991)
Computers are widely used in process monitoring and data acquisition system. There are advantages in using computers because the software packages can be designed according to requirements of any industrial equipment. The functionalities usually include the following: 1) Graphic display of the process 2) Alarm and event management 3) Real time and historical trending 4) Report generation 5) I/O interface driver and communication facilities In this project, a process monitoring and data acquisition software package is developed for IBM PC-AT compatible computers. The software package is written in Turbo Basic.